Penggunaan Model Pembelajaran Kooperatif Tipe Nht Dalam Pembelajaran Ips Untuk Meningkatkan Hasil Belajar Siswa Kelas V Sdn 05 Enano - Akbar Alam (Prodi PGSD Unsultra, 2021)
The purpose of this study was to improve the learning outcomes of Grade V students at SDN 05 Enano, Kabaena Tengah District, Bombana Regency, through the Cooperative Learning Model Type Numbered Heads Together (NHT) in the Social Studies subject. The factors examined in this research were teacher and student activities. The implementation of this classroom action research consisted of two cycles, following the procedures of (1) planning, (2) implementation and observation, (3) evaluation, and (4) reflection. The data collected included qualitative data in the form of teacher and student observation results using observation sheets, and quantitative data obtained from tests at the end of each cycle. The results showed that students’ learning outcomes improved from Cycle I, where learning mastery reached 60%, to Cycle II, which increased to 85%, with a 25% improvement. The average score for Social Studies learning outcomes was 72, with 3 students not yet achieving the minimum mastery criteria (KKM). The improvement in teacher teaching activities also increased from 71.43% in Cycle I to 85.71% in Cycle II, showing a 14.28% increase.